Penerapan Ice Breaker dan Pengaruhnya Terhadap Hasil Belajar Tematik pada Tema 8 Peserta Didik Kelas IV Sekolah Dasar Negeri 15 Salolo Kota Palopo - Rosmalah Yanti; Desi Nasriana Putri (Cokroaminoto Journal of Primary Education, 2020)
This study aims to determine (1) the science learning outcomes before the application if ice breakers on the science learning outcomes of students in class IV SD Negeri 15 Salolo, Palopo City, (2) the effect of applying ice breakers on teh science kearning outcomes of students in class IV SD Negeri 15 Salolo,(3) the significant effect between the application of ice breakers onthe science learning outcomes. This research is a pre experimental research that involves one class. Sampling technique used was simple random sampling. Data were collected through a pretest before learning with Ice Breaker and posttest after learning with ice breaker was applied. The results of this study that the sudents science learning outcomes before the ice breaker was applied for the t-test using a significant level 0f 0,05 (4,603≥1,725) so H0 is rejected and H1 is accepted, it means that the average posttest learning outcomes taught by the application of ice breaker have a significant effect. Thus, it can be concluded that there is an effect of ice breaker learning on the science learning outcomes of grade IV SDN 15 Salolo Palopo City, Sulawesi Selatan